Mengungkap Metode Observasi Yang Efektif Menurut Pra-Pengajar EFL - Putri Adinda Pratiwi; Fahima Mashalani; Maulia Hafizhah; Azra Batrisyia Sabrina; Nur Hapsi Harahap; Deasy Yunita Siregar (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Observation is a process of systematic observation of human activities and physical settings where these activities take place continuously from a natural locus of activity to produce facts. This research uses a qualitative approach to describe and explain the choice of English as a Foreign Language (EFL) pre-teacher observation method. Through interviews with 10 pre-teaching students, the results show a variety of views regarding observation methods. In general, participant observation dominates as the method that is considered the most effective, because it provides an in-depth understanding of social interactions and group dynamics. Although structural and audio-visual observations receive support, direct involvement in classroom activities is considered to provide a more comprehensive understanding. The research results provide valuable insights for English language education practitioners. In conclusion, participant observation is the most relevant method for EFL pre-teaching analysis. Research supports the selection of observation methods that are appropriate to the context and research objectives to ensure the validity and relevance of observation results. Suggestions for further research include considering more specific observation methods, addressing the potential influence of observers in participant observation, and developing more contextual measurement instruments.